Simondon and enaction: the articulation of life, subjectivity, and technics. (October 2021) - Dereclenne, Emilien
Clear similarities may be found between enaction and Simondon's philosophy of individuation. In this article, and in the wake of recent research in the field of enaction, I argue that Simondon's work is relevant to our understanding of the articulation between life, subjectivity, and technics. In line with John Stewart, I define enaction as the dynamic relation whereby living organisms and their environment co-emerge, a process in which technics is revealed as "anthropologically constitutive." I show that this process is truly enlightened by Simondon's theory of imagination and invention.